Trajectories of Civil Society Leaders in Italy: Individual Careers, Organizational Structures, and Ideological Affiliations - Cecilia Santilli (SAGE Publishing, 2021)
The aim of this paper is to explore the relationship between individual leaders’ career trajectories and organizational structure and identity in Italian civil society organizations (CSOs) active at national level. The analysis in this qualitative study draws on two sets of data, semi-structured interviews with leaders on their career trajectories and their understanding of what it takes to become a leader of a CSO and short biographies of leaders’ career trajectories. Three main representational logics are idenitified: within: multi-level, within: member-organization , and outside: supporting organization . The two first logics are based on a trajectory within the organizations either departing from the local and regional levels of the same organizations or within one or more member organizations. The third logic is based on a trajectory outside the organization that is marked by the ideological affiliation of the president through leading positions in other organizations within the same movement or field.